2005
DOI: 10.1508/cytologia.70.287
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in Mitochondrial Nucleoids during the Transition from Anaerobic to Aerobic Culture in the Yeast Saccharomyces cerevisiae

Abstract: Summary When cells of the yeast Saccharomyces cerevisiae, grown to the stationary phase under anaerobic conditions and having distinctive giant mitochondrial nucleoids (mt-nucleoids), were transferred to aerobic conditions, dynamic changes in the mt-nucleoid morphology were revealed by DAPI-fluorescence microscopy. Within 1 h after transfer, the giant mt-nucleoids rapidly elongated into stringlike forms. Within 3 h after transfer, the mt-nucleoids dispersed as small particles in the cytoplasm. Within 6 h after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…4BCD). 81 ) The highly aggregated mt-nucleoids could be isolated from anaerobically grown cells with sucrose gradient centrifugations. 82 ) This indicated that the highly aggregated mt-nucleoids observed by DAPI staining are not the apparent assembly of small mt-nucleoids.…”
Section: Dynamic Changes In Size and Number Of Mt-nucleoidsmentioning
confidence: 99%
“…4BCD). 81 ) The highly aggregated mt-nucleoids could be isolated from anaerobically grown cells with sucrose gradient centrifugations. 82 ) This indicated that the highly aggregated mt-nucleoids observed by DAPI staining are not the apparent assembly of small mt-nucleoids.…”
Section: Dynamic Changes In Size and Number Of Mt-nucleoidsmentioning
confidence: 99%
“…These two species of proteins were also reduced in highly aggregated mt-nucleoids in rho + cells grown anaerobically. The amounts of these two proteins increased in the mt-nucleoid fractions, when anaerobically grown cells were transferred to aerobic conditions, accompanying the morphological changes of mt-nucleoids from aggregated forms to small spherical ones (Shiiba, Miyakawa and Sando 2005). These results suggested that at least two species of the mt-nucleoid proteins might be involved in morphological changes in mt-nucleoids.…”
Section: Discussionmentioning
confidence: 79%
“…Recently, it has been reported that yeast cells alter the protein composition of mt-nucleoids depending on culture medium (fermentative or non-fermentative) (Kucej et al, 2008), and culture conditions (aerobic or anaerobic) (Shiiba et al, 1997(Shiiba et al, , 2005. The size and DNA content of individual mt-nucleoids also vary depending on the culture condition of cells .…”
Section: Morphology and Stability Of The Mt-nucleoids In A δAbf2 Mutantmentioning
confidence: 99%